2006
DOI: 10.1111/j.1553-2712.2006.tb01716.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of Quantitative D-dimer Assays in Identifying Pulmonary Embolism: Implications from a Sequential Decision Model

Abstract: In patients in whom PE is suspected, when CTA is available, even the most sensitive quantitative D-dimer assay is not likely to be cost-effective. When CTA is not available or if its performance is markedly degraded, use of the D-dimer assay has value in combination with CUS and a pulmonary imaging study. These conclusions may not hold for the larger domain of patients presenting to the ED with chest pain or shortness of breath in whom PE is one of many competing diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…In our two-center study of ED patients with suspected PE, we found that the tandem use of D-dimer and MPO had the potential to decrease the number of patients subjected to unnecessary pulmonary imaging by 13% while remaining 100% sensitive. Duriseti et al 15 recently concluded that Ddimer screening was not a cost-effective method of screening patients with suspected PE at institutions where CT with venography is available, because of the limited specificity of D-dimer screening. However, the alternative strategy of simply imaging patients without an initial screening step would seem likely to increase the number of patients subjected to unnecessary pulmonary vascular imaging with its risks from contrast and radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our two-center study of ED patients with suspected PE, we found that the tandem use of D-dimer and MPO had the potential to decrease the number of patients subjected to unnecessary pulmonary imaging by 13% while remaining 100% sensitive. Duriseti et al 15 recently concluded that Ddimer screening was not a cost-effective method of screening patients with suspected PE at institutions where CT with venography is available, because of the limited specificity of D-dimer screening. However, the alternative strategy of simply imaging patients without an initial screening step would seem likely to increase the number of patients subjected to unnecessary pulmonary vascular imaging with its risks from contrast and radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This threshold is based on the manufacturer recommendations and is consistent with the values used clinically at the study hospitals for the purpose of screening patients for PE. [13][14][15] The optimal test threshold for the tandem test (MPO or CRP) was determined as the value resulting in 100% sensitivity within the subset of patients with a positive D-dimer, and we report change in specificity for the following tandem combinations: 1) D-dimer and MPO and 2) D-dimer and CRP compared to the D-dimer alone. Diagnostic performance was assessed by diagnostic indexes from 2 · 2 contingency table analyses and areas under the receiver operating characteristic curves.…”
Section: Discussionmentioning
confidence: 99%
“…For each of these six possibilities, we considered ten imaging strategies (including three different cutoffs for a VQ scan, which we denote as Low, Normal, and Intermediate) 30 (Figure 2). Figure 3 depicts the clinician’s assessment and decision sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Cutoff III (500 mcg/L) represents the current widely employed cutoff for the VIDAS ™ ELISA D-dimer (Table 2). 14, 16, 30, 37, 4042, 44, 7780 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation